Cruising for parking: New empirical evidence and influential factors on cruising time - Jinwoo (Brian) Lee; Duzgun Agdas; Douglas Baker (Journal of Transport and Land Use)
The goal of this study is to explore the perceptions and behaviors of drivers who cruise for parking. We conducted surveys with drivers in Brisbane, Australia, to understand potential factors that influence drivers’ cruising behavior. This study reveals that errors in drivers’ perception of parking cost are one of the leading factors encouraging drivers to cruise for on-street parking. Drivers are not necessarily well informed about parking costs, even when they claim to be familiar with these costs. The survey also reveals that the more informed drivers are about the local traffic and parking conditions, the less likely they are to cruise for extended periods of time. This finding demonstrates the value of traffic and parking information to effectively mitigate cruising for parking. The interview results also demonstrate that the on-street parking premium (i.e., accessibility or convenience factor) could be much larger than our common assumptions and a significant contributor to increased cruising time. Finally, this study introduces the sunk cruising cost and its potential impact on cruising time. Our hypothesis is that the effect of the sunk cost may manifest in a greater tendency for drivers to continue cruising because the time spent cruising is simply unrecoverable past expenditure. The survey data supports our hypothesis, and with findings on the drivers’ misperception about parking cost and the familiarity factor, this result highlights the value of accurate and timely parking cost and availability of information to drivers to tackle the cruising-for-parking issue.